Quality and Flavor Analysis of 14 Kinds of Commercially Available Hemp Pepper Chicken - Cong LIU; Xin LIU; Peng WANG; Xinglian XU; Yin WANG; Jianchao LI (Shipin gongye ke-ji)
To clarify the quality characteristics and flavor characteristics of hemp pepper chicken products, 14 different kinds of commercially available hemp pepper chicken (represented by the letters A~N) were used as the research objects, and their color, texture, shear force, electronic nose, volatile flavor substances and electronic tongue were determined. Meanwhile, the correlation between the sensory evaluation indexes and the instrumental analysis indexes was further explored in conjunction with the sensory evaluation. The results showed that the hardness of 14 kinds of hemp pepper chicken breast ranged from 1742.81 to 4587.54 g, and the shear force ranged from 14.41 to 35.07 N. The hardness of the chicken thighs ranged from 797.09 to 3389.61 g, and the shear force ranged from 7.70 to 26.34 N. The electronic nose evaluation's findings indicated that the nitrogen oxides, inorganic sulfides, organic sulfides, and short-chain alkanes were the main volatile odor constituents of the 14 kinds of hemp pepper chicken. The results of gas chromatography-ion mobility spectrometry (GC-IMS) showed that overall coordination of the aroma of the chicken itself and spices contributed to the formation of the flavor of hemp pepper chicken. Seventy-seven volatile compounds were identified in 14 kinds of hemp pepper chicken. Combined with orthogonal partial least squares discriminant analysis (OPLS-DA), it was found that 26 substances such as butanal, linalool, alpha-pinene, ethyl acrylate, alpha-terpineol, 2-heptanone, 1-octen-3-ol were the characteristic flavor substances of hemp pepper chicken products. The freshness and saltiness were the main factors influencing the taste of hemp pepper chicken. The correlation analysis results revealed that the overall liking index in the sensory evaluation showed a highly significant positive correlation with butanal, linalool, alpha-pinene, ethyl acrylate, alpha-terpineol, 2-heptanone, 1-octen-3-ol, W5S, W1W, W2W, W1S, saltiness, L* and b* response values (P<0.01). This study can serve as a reference for the research and regulation of the flavor quality of hemp pepper chicken products, the selection of raw and auxiliary materials, and the improvement of the industrialization level of hemp pepper chicken products.